CORRELATION OF PHYSICAL ACTIVITY WITH TOTAL CHOLESTEROL RATIO TO HIGH-DENSITY LIPOPROTEIN IN HYPERTENSION ELDERLY AT PUSKESMAS GEDANGAN SIDOARJO - Vincentia Chrestella Amadea W; Mulya Dinata; Dyana Sarvasti (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Background: The elderly have a higher risk of developing hypertension. The elderly will experience a decrease in physical activity due to a decrease in stamina and body strength due to aging. This situation can increase the risk of non-communicable diseases such as coronary heart disease (CHD) and affect blood cholesterol levels in the body. Objective: This study aimed to understand the correlation of physical activity intensity with the ratio of total cholesterol to HDL in hypertension elderly at Puskesmas Gedangan Sidoarjo.Methods: This study is an analytic study with the research subjects elderly with hypertension at the Puskesmas Gedangan Sidoarjo with a cross-sectional study design. Using Spearman's correlative test with the Statistical Product and Service Solution (SPSS) program, data analysis was carried out. Results: There is a negative correlation between physical activity and the ratio of total cholesterol to HDL in the elderly with hypertension with p = 0.004 (<0.05) and the correlation value (τ) = -0.424, which indicates a sufficient correlation value. Of 45 respondents, 11 people (24.4%) had low physical activity intensity, 21 people (46.7%) had moderate physical activity intensity, 13 people had (28.9%) heavy physical activity intensity, 29 people (64.4%) had a total cholesterol/HDL ratio ≤ 5, and 16 people (35.6%) had a total cholesterol/HDL ratio >5. Conclusion: There is a negative correlation between physical activity intensity and the ratio of total cholesterol to HDL in the elderly with hypertension at Puskesmas Gedangan Sidoarjo, which means the higher the intensity of physical activity carried out by the hypertensive elderly, the lower the total cholesterol/HDL ratio.